1988
DOI: 10.1111/j.1945-5100.1988.tb00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectra of Shocked Minerals 1: Olivine

Abstract: Abstract— The Raman spectrum of olivine contained in a chip of the Twin Sisters Peak dunite shocked to 22.2 GPa is essentially identical to the spectrum of unshocked olivine in this rock. The Raman spectra of a powder of the rock shocked to 20.1 GPa and of chips shocked to 59.5 GPa and 60.7 GPa show strong and broad low‐frequency features with crests at 475 cm−1, 556 cm−1, and 572 cm−1, and strong as well as broad high‐frequency features near 1100 cm−1. We conclude that these features are most likely due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In both studies, olivine was used as the shock indicator. The broad feature at 1100 cm −1 , initially thought to be due to the formation of "olivine glass" (Heymann and Cellucci 1988), was absent in the olivine spectra of all chondrites. The shocked meteoritic olivine spectra were almost identical to the spectra of the unshocked olivine, and it was concluded that the absence of the 1100 cm −1 Raman band and the strong luminescence in the heavily shocked chondrite samples were a result of thermal annealing due to fairly slow cooling from the initial shock temperatures.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In both studies, olivine was used as the shock indicator. The broad feature at 1100 cm −1 , initially thought to be due to the formation of "olivine glass" (Heymann and Cellucci 1988), was absent in the olivine spectra of all chondrites. The shocked meteoritic olivine spectra were almost identical to the spectra of the unshocked olivine, and it was concluded that the absence of the 1100 cm −1 Raman band and the strong luminescence in the heavily shocked chondrite samples were a result of thermal annealing due to fairly slow cooling from the initial shock temperatures.…”
Section: Introductionmentioning
confidence: 87%
“…Many petrographic studies on naturally and experimentally shock-metamorphosed minerals have been conducted (e.g., with regard to olivine, Stˆffler 1972;Reimold and Stˆffler 1978;Bauer 1979;Stˆffler et al 1991;Bischoff and Stˆffler 1992). In contrast, Raman and infrared spectroscopic studies of shocked olivine (Besson et al 1982;Heymann and Cellucci 1988;Durben et al 1993;Miyamato and Ohsumi 1995) are still limited, and they do not yet provide conclusive information on the exact shift in wave number or broadening of full width at half maximum (FWHM) values that can be expected for a specific olivine composition at a given shock pressure. Although the published experimental work covers a large pressure range (0-133 GPa), individual studies often did not report the actual wave number shifts in the Raman lines for shocked olivine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Englert et al (1980) detected a shift to higher wavelength in the position of the Raman line under compressive forces. Heymann & Cellucci (1988) specifically compared the Raman spectra of chondritic laboratory-impacted olivines and non-impacted olivines. For a pressure of 22.2 GPa, the two were identical.…”
Section: (A) Shock Grade Of the Samplesmentioning
confidence: 99%
“…Such deformations can be studied with Raman spectroscopy. Several authors have used this technique to evaluate crystal deformation in highly shocked meteorites (Englert et al 1980;Heymann & Cellucci 1988;Heymann 1990;Chen & Xie 1992;Miyamoto & Ohsumi 1995;Hezel et al 2008;Weselucha-Birczynska & Zmudzka 2008; among others), but no specific Raman studies have been performed on minerals from weak-to-moderately shocked chondrites to our knowledge.…”
Section: Introductionmentioning
confidence: 99%